Chronic Aphthous Stomatitis in Young People - Khaydarova Durdona Munisovna (American Journal of Biology and Natural Sciences, 2025)
Chronic aphthous stomatitis (CAS) represents a prevalent oral mucosal disorder in adolescents and young adults, characterized by recurrent, painful ulcerations with significant impact on nutrition, speech, and quality of life. Etiology involves multifactorial interactions including genetic predisposition, immune dysregulation, nutritional deficiencies, microbiota imbalance, and psychological stress. This article examines epidemiology, clinical presentation, immunopathogenesis, diagnostic approaches, and therapeutic strategies, highlighting recent advances in understanding cytokine involvement, T-cell regulation, and topical and systemic interventions. Evidence indicates that early identification and individualized management improve symptom control, reduce recurrence frequency, and enhance functional and psychosocial outcomes in affected populations. Chronic aphthous stomatitis (CAS) represents a recurrent oral mucosal disorder predominantly affecting adolescents and young adults, characterized by painful ulcerations that impair nutrition, speech, and psychosocial wellbeing. Etiology involves complex interactions among genetic predisposition, immune dysregulation, nutritional deficiencies, microbial factors, and psychological stress. This study examines clinical patterns, immunopathogenesis, biochemical alterations, and therapeutic outcomes in affected populations, highlighting cytokine imbalances, T-cell dysfunction, and epithelial barrier compromise. Evidence demonstrates that integrated management combining topical anti-inflammatory therapy, systemic immunomodulation, microbiota control, and targeted nutritional supplementation significantly reduces ulcer frequency, accelerates mucosal healing, and improves functional and quality-of-life indicators, providing a framework for individualized clinical intervention and long-term disease management.